FAKTOR-FAKTOR YANG MEMPENGARUHI REGENERASI PETANI PADI DI DESA DAYEUHLUHUR KECAMATAN DAYEUHLUHUR KABUPATEN CILACAP, JAWA TENGAH - Hani Naziah; D Yadi Heryadi; Dona Setia Umbara; Ristina Siti Sundari (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
The regeneration process of rice farmers is critical and necessary to maintain, improve or develop rice farming as well as for the sustainability of rice farming in the future when the condition of rice farmers is getting older. The needs of interest of the younger generation in Dayeuhluhur village in the field of rice farming are in the category of lack of interest. The purpose of this study was to Find out how education, the younger generation's experience, income, and parent's land area; how the more youthful generation's interest in rice farming; influence of education, young generation's experiences, revenue, and land area parents on the regeneration of rice farmers. The study used a quantitative descriptive approach and data collection by methods, documentation, and questionnaires help. The research sample is 67 respondents and the younger generation with 16 – 30 years old criteria, using purposive sampling technique and the analysis model using multiple linear regression. The result of this study explained that (1) the condition of the education of the younger generation was in the medium category, the experience of the younger generation was in the high category, the parent income was in the high category, and the parent's land area was in the medium category, (2) the condition of the interest of the younger generation in the field of rice farming was included in the moderate category and (3) the regeneration of rice farmers separately or jointly was influenced by factors of education of the younger generation, the experience of the younger generation, parents income, and parents land area.